On Numerical Solutions of Two-Dimensional Boussinesq Equations by Using Adomian Decomposition and He's Homotopy Perturbation Method - Mohyud-Din, Syed Tauseef; İnç, Mustafa; Cavlak, Ebru (Prairie View A & M Univ, Dept Mathematics, 2010)
In this paper, we obtain the approximate solution for 2-dimensional Boussinesq equation with initial condition by Adomian's decomposition and homotopy perturbation methods and numerical results are compared with exact solutions.
Keywords: Boussinesq equations; Adomian's polynomials; nonlinear problems; homotopy perturbation; error estimates